The effects of saltwater on the corrosion behavior and microstructure of low-carbon steel submerged arc welding (Sebha University Conference Proceedings, 2025)
This This study provides a comprehensive examination of corrosion mechanisms and microstructural changes in submerged arc welded (SAW) low-carbon steel (DIN 17100) under simulated saltwater conditions. Through controlled welding parameters (current: 320-380 A; voltage: 27-28 V; travel speed: 31-37 cm/min) using two distinct agglomerated fluxes (ETC FXA 28R and 300IR), Electrochemical assessments demonstrated markedly superior corrosion resistance in 300IR flux specimens (0.132 × 10⁻³ mpy) compared to FXA 28R counterparts (0.485 × 10⁻³ mpy), attributable to enhanced slag-metal interactions and diminished porosity. Microstructural analyses revealed preferential grain boundary pitting in the heat-affected zone (HAZ), with FXA 28R samples exhibiting 23% greater pit density associated with chromium depletion (0.0584 wt.%). Additionally, mechanical evaluations confirmed exceptional microhardness stability (ΔHV < 5%) across all weld regions post-immersion: weld metal (190-210 HV), HAZ (185-200 HV), and base metal (170-198 HV), validating structural integrity preservation in marine environments.